Full-speed scalability of the pDomus platform for DHTs - Rufino, José (2008)
Domus is an architecture for Distributed Hash Tables (DHTs) tailored to a shared-all cluster environment. Domus DHTs build on a (dynamic) set of cluster nodes; each node may perform routing and/or storage tasks, for one or more DHTs, as a function of the node base (static) resources and of its (dynamic) state. Domus DHTs also benefit from a rich set of user-level attributes and operations. pDomus is a prototype of Domus that creates an environment where to evaluate the architecture concepts and features. In this paper, we present a set of experiments conduced to obtain figures of merit on the scalability of a specific DHT operation, with several lookup methods and storage technologies. The evaluation also involves a comparison with a database and a P2P-oriented DHT platform. The results are promising, and a motivation for further work.